Can the Merdeka Belajar curriculum really improve students’ reading literacy? - Zaim, M.; Zakiyah, Muflihatuz (JOALL (Journal of Applied Linguistics and Literature), 2024)
Merdeka Belajar curriculum is the brand-new curriculum implemented in Indonesia in response to the low reading literacy of students. Many discussed the features and the implementation of the Merdeka Belajar curriculum and claim that implementing the current curriculum is effective in improving students' reading literacy due to its features, such as simpler yet in-depth materials and flexible time for learning outcome accomplishment; however, there is not yet any empirical evidence provided to prove the claim. This descriptive research was undertaken to provide empirical evidence of that claim as the curriculum has just been implemented. Twelve teachers across senior high schools in West Sumatera were willingly involved in this study. The data were collected through a written interview, in which the teachers answered ten relevant questions. Their responses about the implementation of the Merdeka Belajar curriculum were analyzed qualitatively. The findings established new facts that answered the research question from the teachers' point of view. First, compared to the 2013 curriculum implementation, they did not only see the implementation of the Merdeka Belajar curriculum as advantageous but also disadvantageous. Even few of them found it run-of-the-mill. Second, when implementing the current curriculum, the teacher developed strategies to increase students' reading literacy and interest. They began by supplying multiple materials, designing fun but exhaustive learning instructional activities, varying the assessments, and building reading corners with captivating books to read. Third, after a year of implementation, the students' reading literacy tended to stay the same, even though it did improve a little for some students. These were because the teachers still experienced problems regarding curriculum, school, and time. In summary, implementing the Merdeka Belajar curriculum cannot improve students' reading literacy.